2018
DOI: 10.1128/jvi.00809-18
|View full text |Cite
|
Sign up to set email alerts
|

Surfactin Inhibits Membrane Fusion during Invasion of Epithelial Cells by Enveloped Viruses

Abstract: Because membrane fusion is a crucial step in the process by which enveloped viruses invade host cells, membrane fusion inhibitors can be effective drugs against enveloped viruses. We found that surfactin from can suppress the proliferation of porcine epidemic diarrhea virus (PEDV) and transmissible gastroenteritis virus (TGEV) in epithelial cells at a relatively low concentration range (15 to 50 μg/ml), without cytotoxicity or viral membrane disruption. Membrane fusion inhibition experiments demonstrate that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
96
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(97 citation statements)
references
References 43 publications
0
96
0
1
Order By: Relevance
“…In a previously published study we demonstrated that surfactin has antiviral activity as membrane fusion inhibitor [3]. In order to improve the viral envelope selectivity of surfactin, we designed 10 analogues with altered peptide amino acids, but kept the length of fatty acid chain of 16 carbon atoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previously published study we demonstrated that surfactin has antiviral activity as membrane fusion inhibitor [3]. In order to improve the viral envelope selectivity of surfactin, we designed 10 analogues with altered peptide amino acids, but kept the length of fatty acid chain of 16 carbon atoms.…”
Section: Discussionmentioning
confidence: 99%
“…SLP5 also has two fewer hydrophobic amino acids than surfactin, this reduces the cost of synthesis while having little effect on antiviral activity. Since surfactin has been shown to protect piglets from PEDV challenge [3], the in vivo antiviral properties of surfactin analogues needs to be tested. Furthermore, with respect to the future use of synthetic surfactins to control or ameliorate infection in pigs, the broader spectrum physiological activities of surfactin analogues needs further study and side effects beyond hemolytic toxicity need to be explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last two decades, surfactin has been shown to be anti-bacterial, anti-fungal, and anti-viral (11, 12, 1719). Mechanistically, surfactin’s broad anti-microbial efficacy has been linked to disruption of lipid membranes (13).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, surfactin’s broad anti-microbial efficacy has been linked to disruption of lipid membranes (13). However, more recently, researchers described surfactin’s efficacy against the animal CoV porcine epidemic diarrhea virus (PEDV), and suggested that surfactin inhibited viral-host membrane fusion (19). In contrast to the PEDV results, we found that surfactin treatment disrupted virion integrity, exposing the viral RNA to RNase I mediated degradation (Fig.…”
Section: Discussionmentioning
confidence: 99%